1991
DOI: 10.1128/aem.57.9.2750-2757.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio anguillarum and closely related species isolated from farmed fish in Norway

Abstract: A total of 264 bacterial strains tentatively or definitely classified as Vibrio anguillarum were examined. The strains were isolated from diseased or healthy Norwegian fish after routine autopsy. With the exception of five isolates from wild saithe (Pollachius virens), the strains originated from nine different species of farmed fish. The bacteria were subjected to morphological, physiological, and biochemical studies, numerical taxonomical analyses, serotyping by slide agglutination and enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 53 publications
2
57
1
1
Order By: Relevance
“…External clinical signs of moribund turbot were similar to an epizootic produced by V. anguillarum reported by Horne, Richards, Roberts & Smith (1977), The start of the present epizootic in turbot was associated with a sudden rise in water temperature. This increase in temperature could favour the invasion of the Vibrio strain in turbot previously debilitated by this stress situation, as reported by several authors (Wedemeyer 1970;Devesa et al 1989;Lupiani et al 1989;Myhr et al 1991;Fouz et al 1992), II turbot and rainbow trotit with ( >tic was V. splendidus biotype I. ink Dr Ju; stela, for tli…”
Section: Pathogenicity Testsmentioning
confidence: 56%
“…External clinical signs of moribund turbot were similar to an epizootic produced by V. anguillarum reported by Horne, Richards, Roberts & Smith (1977), The start of the present epizootic in turbot was associated with a sudden rise in water temperature. This increase in temperature could favour the invasion of the Vibrio strain in turbot previously debilitated by this stress situation, as reported by several authors (Wedemeyer 1970;Devesa et al 1989;Lupiani et al 1989;Myhr et al 1991;Fouz et al 1992), II turbot and rainbow trotit with ( >tic was V. splendidus biotype I. ink Dr Ju; stela, for tli…”
Section: Pathogenicity Testsmentioning
confidence: 56%
“…This finding indicates that these heterogenous bacteria are a normal microbiota of fish and sea water, contaminating the samples rather than acting as opportunistic pathogens. Myhr, Larsen, Lillehaug, Gudding, Heum & Håstein (1991) found V. splendidus biovar I in samples from healthy salmonid fish and incidentally in low numbers from mixed cultures from the kidneys of salmonid fish suffering another major bacterial or viral disease. In the same study, V. splendidus was found in diseased turbot and sea bass in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that V. splendidus is involved in infections in turbot (Myhr, Larsen, Lillehaug, Gudding, Heum & Håstein 1991;Pazos, Santos, Magariños, Bandin, Núñez & Toranzo 1993;Angulo, Lopez, Vicente & Saborido 1994;Gatesoupe et al 1999;Thomson 2001;Thomson et al 2005) and oysters (Gay, Renault, Pons & Le Roux 2004;Le Roux et al 2007). In isolates from moribund turbot, Gatesoupe et al (1999) and Thomson et al (2005) were only able to distinguish between pathogenic and non-pathogenic isolates of V. splendidus by their effects on larval turbot and not from physiological and biochemical properties.…”
Section: Discussionmentioning
confidence: 99%